2020
DOI: 10.1186/s13023-020-01544-z
|View full text |Cite
|
Sign up to set email alerts
|

Patient reported outcome measures in a large cohort of patients with type 1 Gaucher disease

Abstract: Background It is now acknowledged that the input of patients in health outcome assessment is vital to understanding the impact of diseases and interventions for those diseases. This study is the first report of patient-reported outcome measures (PROM) in a large cohort of patients with type 1 Gaucher disease (GD1) enabling us to study predictors of the reported outcomes. Method The PROM was sent via a mobile phone survey to 405 adult patients with GD1. Demographics, clinical data, and treatment status were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Currently, the effective therapy for GD patients, such as enzyme replacement therapy and substrate reduction therapy, which must be administered continually, are extremely costly for patients and caregivers [ 8 , 9 ]. Further, caregivers may experience workdays loss, absenteeism, and job changes while caring for their patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the effective therapy for GD patients, such as enzyme replacement therapy and substrate reduction therapy, which must be administered continually, are extremely costly for patients and caregivers [ 8 , 9 ]. Further, caregivers may experience workdays loss, absenteeism, and job changes while caring for their patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this analysis have confirmed the need to include additional questions in the current PROM questionnaires that address the impact of neurological symptoms, the burden caused by these symptoms, and patient needs related to social support systems. The current questionnaire for patients with type 1 GD has no questions related to current symptoms, including neurological symptoms, caused by GD [ 13 , 14 ]. As patients with types 2 and 3 GD are generally younger than those with type 1, this study has also provided insights into the burden associated with GD that may be specific to the daily lives of younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of QOL in the management of patients with GD, limited information is available on the burden of nGD in patients and caregivers, as qualitative studies conducted to date have almost exclusively included patients with type 1 GD [ 9 11 ]. Although GD-specific patient-reported outcome measures (PROMs) have been developed, these questionnaires are focused on patients with type 1 GD [ 12 14 ] and are not suitable for capturing symptoms and comorbidities of patients with nGD. In addition, although a caregiver-reported outcome measure is currently under development for other lysosomal diseases, there is no such tool for caregivers of patients with GD [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…25 In a first study of GD-specific patient-reported outcome in a relatively large cohort of adult patients, we have recently reported that despite the known association between GD and cancer, mainly myeloma, almost two-thirds of patients reported a lack of concern about this risk. 26 The use of PC is based on the recognition that beyond a glycolipid storage disease, GD is also a protein-misfolding disorder, 27 and the proof of concept was reported in 2013. 28 Unfortunately, because ambroxol is inexpensive and exists in different generic formulations, a formal pharmaceutical company-sponsored clinical trial has not been performed.…”
Section: Case Report Part 4: Gd and Monoclonal Gammopathy Of Undetermined Significancementioning
confidence: 99%